How to Manage COVID-19 Vaccination in Immune-Mediated Inflammatory Diseases: An Expert Opinion by IMIDs Study Group - Ferretti, Francesca; Cannatelli, Rosanna; Benucci, Maurizio; Carmagnola, Stefania; Clementi, Emilio; Danelli, Piergiorgio; Dilillo, Dario; Fiorina, Paolo; Galli, Massimo; Gallieni, Maurizio; Genovese, Giovanni; Giorgi, Valeria; et al. (Frontiers in Immunology, 2021)
Since March 2020, the outbreak of Sars-CoV-2 pandemic has changed medical practice and daily routine around the world. Huge efforts from pharmacological industries have led to the development of COVID-19 vaccines. In particular two mRNA vaccines, namely the BNT162b2 (Pfizer-BioNTech) and the mRNA-1273 (Moderna), and a viral-vectored vaccine, i.e. ChAdOx1 nCoV-19 (AstraZeneca), have recently been approved in Europe. Clinical trials on these vaccines have been published on the general population showing a high efficacy with minor adverse events. However, specific data about the efficacy and safety of these vaccines in patients with immune-mediated inflammatory diseases (IMIDs) are still lacking. Moreover, the limited availability of these vaccines requires prioritizing some vulnerable categories of patients compared to others. In this position paper, we propose the point of view about the management of COVID-19 vaccination from Italian experts on IMIDs and the identification of high-risk groups according to the different diseases and their chronic therapy.